Universiti Utara Malaysia Network Performance Study - Shariful Hafizi, Md. Hanafiah (2004)
Early in 90's the emergence of computer networks had brought great impact in many aspects. The emergence and rapid growth of the computer networks (LAN, WAN, MAN, etc.) need to be manage from here the network management terms evolve and been use widely. Performance management is one of the subclass/subcategory in network management. The network performance needs to be considering start from the logical design of computer networks and when the network is deploy. The network performance itself does not end on the paper when it has been planned but the network performance also need to be monitor and analyzed periodically in order to maintain its performance and 'health'. In this paper network performance study on the UUM network been executed in order to examine and determine that the deployed campus networks are performing at at the optimum level periodically. The UUM network plays an important role because the university administration and education use computer widely in every aspects. The study only emphasize or concentrate onto the network utilization of UUM campus network.